Synthesis and Optimization of Visible Light Active BiVO4 Photocatalysts for the Degradation of RhB - Rong Ran; Joanne Gamage McEvoy; Zisheng Zhang (International Journal of Photoenergy)
Monoclinic BiVO4 powders were synthesized via a novel route using potassium metavanadate (KVO3) prepared by calcination of K2CO3 and V2O5 as a starting material and followed by hydrothermal treatment and were investigated for the degradation of Rhodamine B (RhB) under visible light irradiation. The synthesized BiVO4 particles were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), and UV-Visible (UV-Vis) light diffuse reflectance spectrophotometry. The synthesis produced pure monoclinic BiVO4 particles with multimorphological features containing flower-like, flake-ball, flake, cuboid-like, and plate-like shapes and exhibited strong absorption in the visible light range. The BiVO4 prepared via KVO3 possessed excellent photocatalytic activity for the degradation of RhB under visible light. The performance of this catalyst was found to be superior to other BiVO4 photocatalysts prepared via ammonium metavanadate (NH4VO3) using coprecipitation, combustion, and calcination methods reported in literature, respectively.